2014
DOI: 10.1186/1476-072x-13-43
|View full text |Cite
|
Sign up to set email alerts
|

International variation in neighborhood walkability, transit, and recreation environments using geographic information systems: the IPEN adult study

Abstract: BackgroundThe World Health Organization recommends strategies to improve urban design, public transportation, and recreation facilities to facilitate physical activity for non-communicable disease prevention for an increasingly urbanized global population. Most evidence supporting environmental associations with physical activity comes from single countries or regions with limited variation in urban form. This paper documents variation in comparable built environment features across countries from diverse regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
163
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 193 publications
(176 citation statements)
references
References 48 publications
2
163
0
Order By: Relevance
“…This is consistent with the findings and results gathered in other studies (Christiansen, Madsen, Schipperijn, Ersbøll, & Troelsen, 2014;De Meester et al, 2012;Frank et al, 2010;Freeman et al, 2013). Adams et al (2014) concluded that areas with high walkability are characterized by an accumulation of a large number of inhabitants and higher commuting accessibility (e.g., Hong Kong or Bogota in Colombia).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is consistent with the findings and results gathered in other studies (Christiansen, Madsen, Schipperijn, Ersbøll, & Troelsen, 2014;De Meester et al, 2012;Frank et al, 2010;Freeman et al, 2013). Adams et al (2014) concluded that areas with high walkability are characterized by an accumulation of a large number of inhabitants and higher commuting accessibility (e.g., Hong Kong or Bogota in Colombia).…”
Section: Discussionsupporting
confidence: 82%
“…Most studies assess walkability according to street connectivity, residential density and the land-use mix, which experts believe to be most influential. Originally, these correlates were analyzed separately (Boarnet & Sarmiento, 1998), although they were later grouped into a single "walkability index" (Adams et al, 2014;Frank et al, 2010;Frank et al, 2005).…”
Section: Methods Participantsmentioning
confidence: 99%
“…The diversity of the study cities in climate, demographics, 10 and built environments has been documented in previous publications. 18 Present results suggest systematic principles of environments that support physical activity apply on a global scale. 19 Generalisable associations with physical activity were also reported in analyses of selfreported environment measures in the same study.…”
Section: Discussionmentioning
confidence: 99%
“…A description of GIS methods and variables, examples of data sources for each country, comparability evaluations, and descriptive results of variation in GIS-based environmental variables within and across cities has been published. 18 The following variables were adequately comparable across cities and were used in analyses: net residential density, street intersection density, retail and civic land use ratio to buffer area (access to common destinations), public 43 (12) 43 (13) 42 (13) 46 (12) 39 (14) 40 (14) 42 (13) 42 (13) 43 (12) 42 (11) 40 (12) 43 (12) 44 (13) 44 (11) 47 ( transport density, public park density, and distance to nearest transport. Table 2 provides definitions of variables and key terms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation